Pricing and subsidy policies for Bangladesh agriculture - Osmani, Siddiqur Rahman; Quasem, Md. Abul. (Dhaka, Bangladesh : Bangladesh Institute of Development Studies, 1990)
It discusses the growth and structure of Bangladesh agriculture, the pricing policy and development strategy.
Includes bibliographical references: p. 225-233.
occ 18/01/2019
Loans
Keywords: Agricultural prices; Agricultural subsidies